Feasibility Analysis of NDT Methods Using to Estimate the Concrete Strength as Part of Urban Regeneration - Alyamaç, Kürşat Esat; Ulaş, Merve Açıkgenç; Taş, Yavuzhan; Ghafari, Ehsan (Fırat University, 2018)
Most of the countries are placed in a seismic zone which has high activity and has extremely experienced large-scale losses due to several destructive earthquakes such as Turkey. Therefore, governments are seriously trying to produce the projects that will significantly reduce the earthquake effects. The most important part of these projects is urban regeneration. Within the context of urban regeneration activities, renewal of the buildings which have low earthquake-resistant is targeted. While the earthquake resistance level of a building is decided, one of the important steps is the determination of the strength of the building materials. There are many standard NDT methods that will be able to be used to determine the compressive strength. However, it is necessary to choose the appropriate methods in order to quickly and reliably estimate the strength properties of the materials. The purpose of this study is to determine the optimum NDT method for the urban regeneration. So, feasibility analysis was carried out for the standard NDT methods, and the performance of these methods was evaluated based on the cost and the accuracy. The result is the requirement new NDT method which is the practical and efficient for the large-scale projects such as urban regeneration.
Keywords: Engineering; Mühendislik